2022
DOI: 10.1172/jci153604
|View full text |Cite
|
Sign up to set email alerts
|

Selective delivery of low-affinity IL-2 to PD-1+ T cells rejuvenates antitumor immunity with reduced toxicity

Abstract: PD-1 signaling on T cells is the major pathway that limits T cell immunity, but the efficacy of anti–PD-1 therapy has been limited to a small proportion of patients with advanced cancers. We fortuitously observed that anti–PD-1 therapy depends on IL-2 signaling, which raises the possibility that a lack of IL-2 limits anti–PD-1–induced effector T cell expansion. To selectively deliver IL-2 to PD-1 + CD8 + tumor-infiltrating lymphocytes (TILs), we engineered a low-af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 54 publications
(54 reference statements)
3
47
0
Order By: Relevance
“…Several studies reported that material-based aAPC systems have minimal exhaustions [ 9 , 45 ], but the underlying mechanism has not been elucidated yet. We assume this may be due to the sustained delivery of IL-2 by IL-2/Ab/DC@MF, unlike Ab/DC@MF and Dynabead [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that material-based aAPC systems have minimal exhaustions [ 9 , 45 ], but the underlying mechanism has not been elucidated yet. We assume this may be due to the sustained delivery of IL-2 by IL-2/Ab/DC@MF, unlike Ab/DC@MF and Dynabead [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…One potential way to avoid toxicity would be to use intratumoral injection of IL-2 or the use of targeted IL-2 variants. Some examples include the CD25 mimobody that abolishes CD25 binding ( 47 ), as well as variants that target IL-2 to the tumor microenvironment ( 48 ) or to effector CD8 ( 49 ) or PD1-expressing T cells ( 50 ). Taking into consideration a likely higher adverse event rate, one may preferentially test this triple combination immunotherapy in a personalized manner in patients with unfavorable tumor characteristics such as low TMB, low CD4/IL-2, or low IFN-γ signature.…”
Section: Discussionmentioning
confidence: 99%
“…reported that impaired T-cell immunity caused by IL-2 signaling obstruction could be restored by using a low-affinity IL-2 conjugated with anti-PD-1 (PD-1-laIL-2). PD-1-laIL-2, with a higher affinity to PD-1 + CD8+ T cells than to peripheral Treg cells, was able to amplify the dysfunctional tumor-specific CD8 + T cells potently, thus overcoming tumor resistance to ICB ( 111 ). Moreover, Tregs suppress T-cell activity by upregulating the expression level of immune checkpoints.…”
Section: Mechanisms Of Immune Checkpoint Blockade Resistance From The...mentioning
confidence: 99%